Integrated mechanisms of CaMKII-dependent ventricular remodeling - Kreusser, Michael M.; Backs, Johannes (Frontiers in Pharmacology, 2014)
CaMKII has been shown to be activated during different cardiac pathological processes, and CaMKII-dependent mechanisms contribute to pathological cardiac remodeling, cardiac arrhythmias and contractile dysfunction during heart failure. Activation of CaMKII during cardiac stress results in a broad number of biological effects such as, on the one hand, acute effects due to phosphorylation of distinct cellular proteins as ion channels and calcium handling proteins and, on the other hand, integrative mechanisms by changing gene expression. This review focuses on transcriptional and epigenetic effects of CaMKII activation during chronic cardiac remodeling. Multiple mechanisms have been described how CaMKII mediates changes in cardiac gene expression. CaMKII has been shown to directly phosphorylate components of the cardiac gene regulation machinery. CaMKII phosphorylates several transcription factors such as CREB that induces the activation of specific gene programs. CaMKII activates transcriptional regulators also indirectly by phosphorylating histone deacetylases, especially HDAC4, which in turn inhibits transcription factors that drive cardiac hypertrophy, fibrosis and dysfunction. Recent studies demonstrate that CaMKII also phosphorylate directly histones, which may contribute to changes in gene expression. These findings of CaMKII-dependent gene regulation during cardiac remodeling processes suggest novel strategies for CaMKII-dependent "transcriptional or epigenetic therapies" to control cardiac gene expression and function. Manipulation of CaMKII-dependent signaling pathways in the settings of pathological cardiac growth, remodeling, and heart failure represents an auspicious therapeutic approach.